2015
DOI: 10.1097/md.0000000000001872
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Folic Acid on Oxidative DNA Damage

Abstract: Although previous reports have linked DNA damage with both transmissions across generations as well as our own survival, it is unknown how to reverse the lesion. Based on the data from a Randomized, Double-blind, Placebo Controlled Clinical Trial, this study aimed to assess the efficacy of folic acid supplementation (FAS) on DNA oxidative damage reversal.In this randomized clinical trial (RCT), a total of 450 participants were enrolled and randomly assigned to 3 groups to receive folic acid (FA) 0.4 mg/day (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, this DNA damage is not specific for low zinc intake. DNA strand breaks also increase with low intakes of folate and vitamin B-6 ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this DNA damage is not specific for low zinc intake. DNA strand breaks also increase with low intakes of folate and vitamin B-6 ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of FA supplementation in the F1 sperm may be partly explained by its antioxidant activity if the miRNA changes are caused by oxidative stress induced by POPs exposure (i.e. F1 POPs males) [39–41]. If, however, the miRNA changes in POPs exposed sperm are due to an altered methylation capacity or dysregulated nucleotide synthesis or mutations, then the increased availability of methyl groups provided by FA supplementation may mitigate the POPs effect by supporting DNA repair through nucleotide synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of maternal PM exposure and PTD have suggested that oxidative stress could be a potential biological pathway (Moore et al 2018;Li et al 2017;Pereira et al 2014). A randomized clinical trial of 438 healthy adults compared urine 8-hydroxy-2 0deoxyguanosine (8-OHdG/Cr), a marker of oxidative damage to DNA, before and after intervention among three groups-a) FA at 0:4 mg=d for 8 wk; b) FA at 0:8 mg=d for 8 wk; and c) placebo for 8 wk-and found that urinary 8-OHdG/Cr levels were decreased in a dose-related pattern for participants who had FA supplementation (Guo et al 2015). These findings suggest that FA might have a protective effect on PM-related PTD by regulating the imbalance of oxidants and antioxidants as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…2014 ). A randomized clinical trial of 438 healthy adults compared urine 8-hydroxy-2′-deoxyguanosine (8-OHdG/Cr), a marker of oxidative damage to DNA, before and after intervention among three groups— a ) FA at for 8 wk; b ) FA at for 8 wk; and c ) placebo for 8 wk—and found that urinary 8-OHdG/Cr levels were decreased in a dose-related pattern for participants who had FA supplementation ( Guo et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%